Analisis Hukum Islam terhadap Waria Sebagai Penata Rias Wanita di Kota Makassar - Widiyanti, Widiyanti; Jamil, Jamil (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2024)
This study examines the Islamic Law Analysis of the practice of makeup artists for waria in Makassar City. The main issue is how Islamic Law views gender identity and the practice of transvestite makeup artists, as well as how it is implemented in the context of Makassar society. This research uses a qualitative approach with case studies, involving in-depth interviews and observations on the practice of transvestite makeup artists. The results show the complexity of Islamic Law's views on transvestites and makeup artists, which include considerations of ethics, social norms, and religious perspectives. The implications of this research are the need for a deeper understanding of the local context in interpreting Islamic law related to waria and makeup artists, as well as the importance of dialogue between religions, cultures, and human rights in formulating policies that are inclusive and respect gender diversity.